(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: This paper explores the fundamental properties and behavior of sound waves within the realms of physics and astronomy. It examines the mechanisms of sound wave propagation, including their interaction with different media and the influence of various environmental factors. The study further discusses the role of acoustic waves in astrophysical phenomena, such as the oscillations of stellar atmospheres and the detection of cosmic events through sound wave analogues. By integrating theoretical models with observational data, this research highlights the significance of sound waves in understanding both terrestrial and extraterrestrial environments.